THE EFFECT OF HEALTH EDUCATION ON ADOLESCENT KNOWLEDGE ABOUT ANEMIA - Riesmiyatiningdyah Riesmiyatiningdyah; Kusuma Wijaya Ridi Putra; Agus Sulistyowati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Anemia experienced by young women often occurs when they are menstruating. Young women must have knowledge about these conditions, so that they can overcome these problems properly. Objectives: The purpose of this study was to determine the effect of health education on the level of knowledge of adolescents about anemia. Methods: The research design used in this study was pre-experimental with a one-group pre-post test design approach. This research was conducted at the Islamic Boarding School of Tahfizh Putri Alfirdaus Hidayatullah, Sekardangan, Sidoarjo on February 28, 2021. The sampling technique used in this study was total sampling. The number of samples in this study were 24 respondents. This study uses health education materials about anemia for the treatment given and a modified questionnaire from Zulaekah's (2007) knowledge level questionnaire with a Cronbach Alpha value of .594. This research was conducted by providing health education to respondents about anemia. Before the health education was carried out, the researcher conducted a pre-test to measure the respondent's level of knowledge. After the health education was carried out, the researcher conducted a post-test to evaluate the respondents' level of knowledge about anemia. The statistical test carried out in this study is the Wilcoxon Signed Rank Test with significant level ? < 0.05. Results: Based on data analysis using the Wilcoxon Signed Rank Test, it was found that there was an effect of health education on the level of adolescent knowledge about anemia (p-value = .011). Conclusion: It is important to provide health education about anemia to young women, so that they can find out what conditions they experience when they are anemic due to menstruation. Health workers are expected to provide this health education through health counseling or education.